2020
DOI: 10.1001/jamaoncol.2020.1278
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Reduced-Intensity Conditioning Regimens With Overall Survival Among Patients With Non-Hodgkin Lymphoma Undergoing Allogeneic Transplant

Abstract: IMPORTANCE Reduced-intensity conditioning and nonmyeloablative conditioning (RIC-NMAC) regimens are frequently used in allogeneic hematopoietic cell transplant (HCT) for non-Hodgkin lymphoma. However, the optimal RIC-NMAC regimen in allogeneic HCT for non-Hodgkin lymphoma is not known.OBJECTIVE To investigate whether RIC-NMAC regimens at a higher end of the intensity spectrum are associated with increased nonrelapse mortality and lower overall survival compared with RIC-NMAC regimens at the lower end of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…34 The benefits of intensifying conditioning intensity in lymphoma patients are debatable. Similar to previous studies on allo-HCT in other NHL subtypes, 22,[44][45][46][47][48][49] the current study does not show an advantage of high intensity conditioning regimens for the first time also for mature nodal T-cell NHL in a large dataset.…”
Section: Discussionsupporting
confidence: 87%
“…34 The benefits of intensifying conditioning intensity in lymphoma patients are debatable. Similar to previous studies on allo-HCT in other NHL subtypes, 22,[44][45][46][47][48][49] the current study does not show an advantage of high intensity conditioning regimens for the first time also for mature nodal T-cell NHL in a large dataset.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the CIBMTR recently published data regarding the impact of various RIC regimens on HSCT outcomes for NHL patients, and patients who received fludarabine, cyclophosphamide, and 200 cGy of TBI conditioning were among those with the best outcomes, which were superior to outcomes of patients who received more intensive fludarabine-melphalan 140 mg/m 2 conditioning. 28 Our findings suggest that, unlike patients with other NHL histologies, patients with CLL might not benefit from TBI-containing regimens. A previous study from Denmark reported that patients with CLL had lower response rates to low doses of radiation at irradiated sites compared with patients with other indolent NHL histologies.…”
Section: Discussionmentioning
confidence: 66%
“…This suggests that the high rate of severe CRS observed in our cohort may be related to the unique combination of using PBSC grafts with FluMel conditioning. One recent study found a higher rate of NRM and decreased OS in patients with NHL receiving FluMel conditioning for allogeneic HCT compared to udarabine and busulfan-based conditioning 13 , whereas another cohort of patients with lymphoma undergoing haplo-HCT with udarabine and cyclophosphamide conditioning did not suffer increased NRM or reduced OS 14 .…”
Section: Discussionmentioning
confidence: 99%